Morphological and environmental varieties of the Cambrian stromatolites in Western Henan, North China Craton - Yu-Guang Chang; Shi-Yun Qing; Ming-Yue Dai; Song-Hua Chen (PLoS ONE, 2025)
Morphological varieties of Cambrian stromatolites in western Henan, North China Craton were essentially related to palaeoenvironmental parameter changes of the marine-floor. Small plexiform, hemispherical-smooth wavy, small columnar, irregular small columnar stromatolites, and stromatolites that surrounding flat-pebble conglomerate limestones are identified, in which the last type of stromatolite is unique, and they possess different macromorphology and micromorphology characteristics. A large number of Girvanella fossils, which were distributed in prostrate or horizontal and winding or overlapping patterns, were preserved in the laminae of stromatolites, and the dark laminae were formed by combined effect of Girvanella and precipitation of calcium carbonate. The research elucidates that small plexiform and small columnar stromatolite developed in the supratidal zone, hemispherical-smooth wavy, small columnar stromatolites, and stromatolites that surrounding flat-pebble conglomerate limestones grew in the intertidal zone with weaker hydrodynamic conditions, as well as irregular small columnar stromatolites occurred in subtidal zone. The features of microscopic laminae of stromatolites are influenced by microorganisms and metazoan, the macroscopic morphologies and growth of stromatolites are affected and controlled by terrigenous materials, hydrodynamic conditions and sedimentary substrates.